Rita Sheehan interviewed by Anne O'Connor in Transfer of Irish folk tradition to Australia collection - Sheehan, Rita.; O'Connor, Anne. (1985)
Sheehan speaks about her Irish parents who came to Australia via America; her visit to Ireland; treatment of Irish in Australia; contribution of Irish to the development of Australia; beliefs relating to spirits, including the Banshee; beliefs and traditions about pregnancy and birth, marriages and death; and Gaelic words and phrases she remembers.
Part of a collection of recordings relating to the Irish contribution to Australian culture and cultural identity.
Recording begins approx 1 min. into reel 13.
Recorded at Hughes, Australian Capital Territory on 1 August 1985.
Digital master available
Time-coded transcript available.
Keywords: Sheehan, Rita -- Interviews; Irish -- Australia; Irish -- Australia -- Social life and customs; Irish -- Australia -- Folklore